2018
DOI: 10.1080/08941939.2017.1411543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Posterolateral Fusion and Posterior Lumbar Interbody Fusion in the Treatment of Lumbar Spondylolithesis: A Meta-Analysis

Abstract: Both these two procedures provide excellent outcomes for patients with spondylolisthesis. There was no significant difference of clinical outcome, complication rate, fusion rate and blood loss between PLIF and PLF techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…As a most applied surgical approach, PLIF is considered superior to other fusion procedures in terms of anterior column support, sufficient decompression of nerve roots, and restoration of lumbar alignment [16]. Several prior studies have reported the effective improvement of clinical efficacy of PLIF for DS [17].…”
Section: Discussionmentioning
confidence: 99%
“…As a most applied surgical approach, PLIF is considered superior to other fusion procedures in terms of anterior column support, sufficient decompression of nerve roots, and restoration of lumbar alignment [16]. Several prior studies have reported the effective improvement of clinical efficacy of PLIF for DS [17].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive pathological evaluation for glioma should include both histopathological and molecular pathological examinations according to the 2016 WHO classification . Special attention should be paid to IDH1 mutation status, which is closely associated with GRE, especially for LGG patients …”
Section: The Diagnostic Process For Grementioning
confidence: 99%
“…20 Special attention should be paid to IDH1 mutation status, which is closely associated with GRE, especially for LGG patients. 12,23 As for the diagnosis of epilepsy, seizure history and clinical signs of epileptic seizures should be conventionally documented for patients with glioma. 2 Moreover, a 2-hour video electroencephalogram (EEG), including a non-rapid eye movement stage I-II sleep EEG, should be performed for patients with definite or possible epileptic seizures.…”
Section: For Grementioning
confidence: 99%
“…Lumbar isthmic spondylolisthesis is an usual low back pain disease with morbidity of 4–6% in the population [1,2]. The character of this disease is the upper vertebrae slips over the subjacent vertebrae because of a defect in the isthmus in adolescence or adulthood [3]. The main symptoms of lumbar isthmic spondylolisthesis are low back pain, paresthesia in lower limbs, weakness of the legs and even impaired ambulation, intermittent claudication, etc [4].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive TLIF (MIS-TLIF), as a novel operation, was firstly described by Foley in 2002 [13], with less complications such as blood loss and soft tissue injury [9,14]. Comparing with open TLIF, this minimally invasive procedure had some advantages in terms of amount of bleeding, operation time, hospitalisation time and fusion rates [3,12]. As a novel technology, O-arm navigation has the advancement by providing real-time intraoperative images of the key operating area to assist surgeons improve the performing accuracy.…”
Section: Introductionmentioning
confidence: 99%